THE DIFFICULTIES WHEN TEACHING ENGLISH TO RUSSIAN CHILDREN IN UZBEKISTAN’S PUBLIC PRIMARY SCHOOLS - Muminova , Sokhiba Nurboboyevna (Innovative Development in Educational Activities, 2023)
Teachers may face difficulties when teaching a foreign language to students from diverse cultural backgrounds. Teaching English as a second language can be particularly difficult in Uzbekistan, which has a diverse range of cultures and languages. This research will investigate the impact of cultural diversity on English teaching in Uzbekistan’s public primary schools, with an emphasis on the difficulties encountered by Uzbek teachers when teaching English to Russian children.